THE EFFECTIVE COMMUNICATION AND SKILLS (International Journal of Food and Nutritional Sciences, 2022)
As Aristotle said “man is a social animal” and in society communication plays a fundamental role in the development of any healthy relationship. Since word ‘communication’ derives from the Latin word ‘communies’ which means ‘common’ and Aristotle rightly asserts that the zeal and zest to communicate with others is common phenomenon among human being's.Communication is to convey the message from one to another. It is an exchange of Ideas among certain community who have mutual understanding.The communication is Central to everything we do, and it is common in all the activities in all walks of life